STRATEGI ELIT DAN PARTISIPASI MASYARAKAT DALAM PENYELENGGARAAN PILKADA MUNA TAHUN 2020 - Sarniati, Sarniati; Dirman, La Ode; Bahtiar, Bahtiar (Universitas Halu Oleo, 2021)
Abstract: The purpose of this research is to identify, analyze and understand the Elite strategies, community participation and the implications of elite strategies and community participation on the results of the Regional Election. The theory used in this research is the theory of social practice by Pierre Bourdieu, methodologically this research is a qualitative research by collecting the data using observation and in-depth interviews technique. The results of this study indicate that the TERBAIK candidate pair fully empowers political elites and party elites in socializing to become campaign teams, empowers volunteer teams and approaches religious elites and civil elites. The pair of candidates for TERBAIK has also built good communication so that they have the full support of two former Muna Regents who still have a strong mass among the Muna community, namely the former Muna Regent for the 2000-2010 period and the former Muna Regent for the 2010-2015 period and other bureaucratic elites in Muna Regency. While the RAPI candidate pair did not empower the political elite and their supporting/supporting parties in socializing, the RAPI candidate pair maximized the teams and volunteers that were formed long before the Regional Election stage began and approached the religious elite and the civil elite. Several traditional and religious leaders were involved in practical politics so that there was disharmony between communities after the determination of the winner. The increasing political participation in the Regional Election is because apart from the vigur of the two pairs of candidates, alsi because of material rewards. In winning a candidate pair, the communication that is built is unconsciously influenced by history and the agreement of the Ancestors, affected by the district (ghoera) and social stratification (kaomu and walaka).Â Keywords: Community Participation, Elite Strategy, Implications, Regional Election Results